Analisa Keamanan Jaringan Wireless Di Sekolah Menengah Al Firdaus - Dewi, Gilang Kumala, Prof. Dr. Budi Murtiyasa, M.Kom, Dedi Gunawan, S.T, MSc (2016)
Al Firdaus Secondary School is one of institution of education and it has wireless media as facility of learning. Wireless is very vulnerable against attack, because wireless is moving through radio wave . the research discussed about network mapping and security of Al Firdaus Secondary School. In order to test network security, author user wireless hacking concept, namely by doing penetration key, sniffing, ARP poisoning, and denial of service attack. With assistance of software consisting of aircrack-ng, commview, netcut, wirelessmon, and wireshark, author was still finding several fault in security of the wireless network of the school . however, network security applied was categorized as 'safe' because most access point installed used security of WPA/WPA2 level.